Flue gas recovery system for natural gas combined heat and power plant with distributed peak-shaving heat pumps. (25th January 2017) - Zhao, Xiling; Fu, Lin; Wang, Xiaoyin; Sun, Tao; Wang, Jingyi; Zhang, Shigang
Highlights: A flue gas recovery system with distributed peak-shaving heat pumps is proposed. The system can improve network transmission and distribution capacity. The system is advantageous in energy saving, emission reduction and economic benefits. Abstract: District heating systems use distributed heat pump peak-shaving technology to adjust heat in secondary networks of substations. This technology simultaneously adjusts the heat of the secondary network and reduces the return-water temperature of the primary network by using the heat pump principle. When optimized, low temperature return-water is able to recycle more waste heat, thereby further improving the heating efficiency of the system. This paper introduces a flue gas recovery system for a natural gas combined heat and power plant with distributed peak-shaving heat pumps. A pilot system comprising a set of two 9F gas-steam combined cycle-back pressure heating units was used to analyse the system configuration and key parameters. The proposed system improved the network transmission and distribution capacity, increased heating capacity, and reduced heating energy consumption without compromising heating safety issues. As such, the proposed system is advantageous in terms of energy saving, emission reduction, and economic benefits.